The role of the private sector in the promotion of the sustainable development agenda : a study case of Japan and Germany - Soares, Frederico Lamego de Teixeira (2023)
Tese (doutorado) — Universidade de Brasília, Instituto de Relações Internacionais, Programa de Pós-Graduação em Relações Internacionais, 2023.